2006
DOI: 10.1001/archpedi.160.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Parents Who Smoke to Prevent Their Children From Initiating Smoking

Abstract: Children in the pre-initiation phase of smoking who receive antismoking socialization from their parents are less likely to initiate smoking, even if their parents smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 33 publications
(64 reference statements)
2
85
1
4
Order By: Relevance
“…Although smoking as a teenager does not predetermine that one' s adolescent children will smoke, [22][23][24][25][26] our longitudinal trajectories reveal that parental smoking at any age (even before the child is born) increases the chances that their children will smoke. Intervention efforts to heighten parental disapproval of smoking and weaken possible intergenerational influences [45][46][47][48][49][50] should target parents who were smokers at any point from adolescence to adulthood. In addition to parents, the smoking behavior of older siblings should be targeted for prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking as a teenager does not predetermine that one' s adolescent children will smoke, [22][23][24][25][26] our longitudinal trajectories reveal that parental smoking at any age (even before the child is born) increases the chances that their children will smoke. Intervention efforts to heighten parental disapproval of smoking and weaken possible intergenerational influences [45][46][47][48][49][50] should target parents who were smokers at any point from adolescence to adulthood. In addition to parents, the smoking behavior of older siblings should be targeted for prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…7 We excluded 3 studies [41][42][43] because their measures of youth smoking were inconsistent with those in the simulation model. We excluded another study 44 because the tobacco intervention was just 1 aspect of an intensive intervention that targeted a range of substance abuse and sexual health behaviors.…”
Section: Effectiveness In Counseling Scenariosmentioning
confidence: 99%
“…Although blinding of outcome assessors was not reported in several trials, this is unlikely to produce bias in studies that used standardized data collection tools, such as computer-assisted telephone interviewing. Three studies did not report baseline participant data by group (27,30,33), which makes ensuring that groups were comparable at baseline difficult. Both medication trials were rated as fair-quality, primarily because of attrition and compliance concerns.…”
Section: Effects Of Interventions On Smoking Prevalence Initiation mentioning
confidence: 99%
“…No primary care-relevant trials were identified that assessed health outcomes or examined subsequent rates of adult smoking. We identified 18 trials (reported in 22 publications) that examined the efficacy of primary carerelevant interventions in preventing tobacco use initiation or promoting cessation among young persons (Appendix Table 1, available at www.annals.org) (15)(16)(17)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). We examined all 18 trials for harms related to the intervention and 1 additional trial (37) that reported the harms of bupropion.…”
mentioning
confidence: 99%